Questions & Answers

Question

Answers

(a) $\dfrac{1}{2}$

(b) $\dfrac{1}{3}$

(c) $\dfrac{1}{4}$

(d) None of these

Answer
Verified

Hint: Taking the given probabilities of A and B events, first find out $P(A),P({{B}^{c}})$. Then using this, find out other probability identities like $P(A\cap {{B}^{c}})$ , etc.

Complete step-by-step answer:

As per the given information, A and B are two events, such that $P({{A}^{c}})=0.3,P(B)=0.4$.

Now we know the probability that an event does not occur is one minus the probability that the event occurs, so

$P({{A}^{c}})=1-P(A)$

Substituting the given value, we get

0.3 = 1 â€“ P(A)

Or, P(A) = 1 â€“ 0.3 =0.7 â€¦â€¦â€¦â€¦.(i)

Similarly, we will find out for event B, i.e.,

$P({{B}^{c}})=1-P(B)$

Substituting the given value, we get

$P({{B}^{c}})=1-0.4=0.6........(ii)$

Now we have to find,

$P\left[ \dfrac{B}{\left( A\cup {{B}^{c}} \right)} \right]$

This can be written as,

$P\left[ \dfrac{B}{\left( A\cup {{B}^{c}} \right)} \right]=\dfrac{P\left[ B\left( A\cup {{B}^{c}} \right) \right]}{P\left( A\cup {{B}^{c}} \right)}.........(iii)$

Observe the denominator, it is the union of event A and non occurring of event B, So

$P\left( A\cup {{B}^{c}} \right)=P(A)+P({{B}^{c}})-P(A{{B}^{c}})$

Now substituting the corresponding values from equation (i), (ii) and given value, we get

$P\left( A\cup {{B}^{c}} \right)=0.7+0.6-0.5=0.8$

Substituting this value in equation (iii), we get

$P\left[ \dfrac{B}{\left( A\cup {{B}^{c}} \right)} \right]=\dfrac{P\left[ B\left( A\cup {{B}^{c}} \right) \right]}{0.8}.........(iv)$

Now we will simplify the numerator by opening the bracket as shown below:

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P\left[ \left( B\cap A \right)\cup \left( B\cap {{B}^{c}} \right) \right]$

But we know intersection of an event occurring and not occurring is one, so the above equation becomes,

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P\left[ \left( B\cap A \right) \right]........(v)$

Now we know,

$\begin{align}

& P\left( A\cap {{B}^{c}} \right)=P(A)-P\left( A\cap B \right) \\

& \Rightarrow P\left( A\cap B \right)=P(A)-P\left( A\cap {{B}^{c}} \right) \\

\end{align}$

Using this in equation (v), we get

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P(A)-P\left( A\cap {{B}^{c}} \right)$

We can write $P\left( A\cap {{B}^{c}} \right)=P\left( A{{B}^{c}} \right)$, so the above equation becomes,

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P(A)-P\left( A{{B}^{c}} \right)$

Substituting the values from equation (i) and the given values, we get

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=0.7-0.5=0.2$

Substituting this value in equation (ii), we get

$P\left[ \dfrac{B}{\left( A\cup {{B}^{c}} \right)} \right]=\dfrac{0.2}{0.8}=\dfrac{1}{4}$

This is the required probability.

Note: Students get confused while applying the formula. Students should learn and understand the concept of probability clearly. Student gets confused to make out that $P\left( A\cap {{B}^{c}} \right)=P\left( A{{B}^{c}} \right)$, and they get stuck to find out the value $P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P(A)-P\left( A\cap {{B}^{c}} \right)$, and wonâ€™t be able to get the answer.

Complete step-by-step answer:

As per the given information, A and B are two events, such that $P({{A}^{c}})=0.3,P(B)=0.4$.

Now we know the probability that an event does not occur is one minus the probability that the event occurs, so

$P({{A}^{c}})=1-P(A)$

Substituting the given value, we get

0.3 = 1 â€“ P(A)

Or, P(A) = 1 â€“ 0.3 =0.7 â€¦â€¦â€¦â€¦.(i)

Similarly, we will find out for event B, i.e.,

$P({{B}^{c}})=1-P(B)$

Substituting the given value, we get

$P({{B}^{c}})=1-0.4=0.6........(ii)$

Now we have to find,

$P\left[ \dfrac{B}{\left( A\cup {{B}^{c}} \right)} \right]$

This can be written as,

$P\left[ \dfrac{B}{\left( A\cup {{B}^{c}} \right)} \right]=\dfrac{P\left[ B\left( A\cup {{B}^{c}} \right) \right]}{P\left( A\cup {{B}^{c}} \right)}.........(iii)$

Observe the denominator, it is the union of event A and non occurring of event B, So

$P\left( A\cup {{B}^{c}} \right)=P(A)+P({{B}^{c}})-P(A{{B}^{c}})$

Now substituting the corresponding values from equation (i), (ii) and given value, we get

$P\left( A\cup {{B}^{c}} \right)=0.7+0.6-0.5=0.8$

Substituting this value in equation (iii), we get

$P\left[ \dfrac{B}{\left( A\cup {{B}^{c}} \right)} \right]=\dfrac{P\left[ B\left( A\cup {{B}^{c}} \right) \right]}{0.8}.........(iv)$

Now we will simplify the numerator by opening the bracket as shown below:

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P\left[ \left( B\cap A \right)\cup \left( B\cap {{B}^{c}} \right) \right]$

But we know intersection of an event occurring and not occurring is one, so the above equation becomes,

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P\left[ \left( B\cap A \right) \right]........(v)$

Now we know,

$\begin{align}

& P\left( A\cap {{B}^{c}} \right)=P(A)-P\left( A\cap B \right) \\

& \Rightarrow P\left( A\cap B \right)=P(A)-P\left( A\cap {{B}^{c}} \right) \\

\end{align}$

Using this in equation (v), we get

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P(A)-P\left( A\cap {{B}^{c}} \right)$

We can write $P\left( A\cap {{B}^{c}} \right)=P\left( A{{B}^{c}} \right)$, so the above equation becomes,

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P(A)-P\left( A{{B}^{c}} \right)$

Substituting the values from equation (i) and the given values, we get

$P\left[ B\left( A\cup {{B}^{c}} \right) \right]=0.7-0.5=0.2$

Substituting this value in equation (ii), we get

$P\left[ \dfrac{B}{\left( A\cup {{B}^{c}} \right)} \right]=\dfrac{0.2}{0.8}=\dfrac{1}{4}$

This is the required probability.

Note: Students get confused while applying the formula. Students should learn and understand the concept of probability clearly. Student gets confused to make out that $P\left( A\cap {{B}^{c}} \right)=P\left( A{{B}^{c}} \right)$, and they get stuck to find out the value $P\left[ B\left( A\cup {{B}^{c}} \right) \right]=P(A)-P\left( A\cap {{B}^{c}} \right)$, and wonâ€™t be able to get the answer.

×

Sorry!, This page is not available for now to bookmark.